Product Photography Training as an Effort to Enhance the Creativity of Visual Communication Design Students at SMK Plus Qurrota A’yun Samarang - Asep Sandi; Ummu Salamah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Product photography is more than just taking pictures of products; it involves incorporating visual design elements and requires specific photography skills to enhance the product's image and market value. In the Visual Communication Design program, students learn communication concepts through creative expression, applied across various visual communication media, including product photography. The goal of this community service activity is to improve the skill level and creativity of students in the Visual Communication Design program at SMK Plus Qurrota A’yun in product photography, broaden their knowledge about professional photography tools, and motivate and develop their potential and interest in product photography. The methods used in this community service include training and mentoring. The training, conducted over four days with 15 participants, provided theoretical and practical product photography instruction. The results of this activity include a better understanding of product photography among students, particularly in practicing product photography, as evidenced by an increase in post-test scores from 40% to 86%. Participants also demonstrated the ability to create photos using their own products.